Missional Identity of a Parish Church: A Case Study from the Church of England - Spencer, Stephen (Journal of Anglican studies, 2013)
This essay draws on the typological framework of Stephen B. Bevans and Roger P. Schroeder in Constants in Context: A Theology of Mission for Today (Maryknoll, NY: Orbis Books, 2004), to analyse a case study church drawn from the Church of England. It investigates key elements of the theology and life of the church, in particular its implicit eschatology and understanding of salvation, and its approach to evangelism, to identify and establish which of Bevans and Schroeder's models it most closely expresses. This correlation is then used to draw out certain practical implications for the life of the church, most notably how it can more consistently and therefore with more integrity live out its inherent approach to mission. This shows the general practical usefulness of this methodology for other churches in different settings.